Pengaruh Motivasi, Disiplin Kerja dan Lingkungan kerja terhadap Karyawan PT. BITNIAGA CIPTA GEMILANG - Masram Masram; Mu’ah Mu’ah; Putri Ismiarsih; Siti Musarofah; Mokhtar Sayyid (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
This study aims to determine the influence of motivation, discipline work and work environment towards employee performance at PT. Bitniaga Copyright Resounding. The type of research used is quantitative research. Method collection of data used in research through disseminated to employees of PT. Bitniaga Cipta Gemilang. Sampling techniques using Total sampling which means that the sample in this study is all population of 87 Respondents. Data analyzed using the SPSS application program for windows version 25. The analysis in this study includes Stastalistic test, validity test, reliability, test classical assumption, normality test, multicollinearity test, heteroskedasticity test, test regression, t test, as well as f test. The results of this study mean that it can be concluded that Work Motivation has a positive and significant effect on performance Employees, so the first hypothesis is accepted, Work Discipline is influential significantly to the performance of Employees. Then it can be concluded that Work Discipline has a positive and significant effect on employee performance, so that the second hypothesis is accepted, the Work Environment is influential in significant to Employee performance. Then it can be concluded that Work Environment has a positive and significant effect on employee performance, so that the third hypothesis is accepted, Work Motivation, Work Discipline and The Work Environment has a significant effect on employee performance. Then it can it is concluded that Work Motivation, Work Discipline and Work Environment positive and significant effect on employee performance, so the hypothesis the fourth is accepted